V0.04-Valuation of jet grouting piles in the northwest area - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the V0.04-Valuation of jet grouting piles in the northwest area of Brac University new campus development project .